Grace and Free Will on Quiescence and Avoiding Semi-Pelagianism - Kittle, Simon ca. 20./21. Jh. (European journal for philosophy of religion, 2022)
Several recent incompatibilist accounts of divine grace and human free will have appealed to the notion of quiescence in an attempt to avoid semi-Pelagianism while retaining the fallen person's control over coming to faith and thus the agent's responsibility for failing to come to faith. In this essay I identify three distinct roles that quiescence has been employed to play in the recent literature. I outline how an account of divine grace and human free will may employ quiescence to play one role without playing either of the others. I also note that getting clear about these roles allows us to see that so-called sourcehood accounts of free will do not need to appeal to quiescence to avoid semi-Pelagianism. Far from being a benefit of sourcehood accounts, however, this highlights a serious defect in such accounts; I draw out this defect, developing it into a general argument against sourcehood accounts of free will.